Unusual fcc-structured Ag10 kernels trapped in Ag70 nanoclusters. Issue 2 (24th October 2018) - Su, Yan-Min; Wang, Zhi; Zhuang, Gui-Lin; Zhao, Quan-Qin; Wang, Xing-Po; Tung, Chen-Ho; Sun, Di
Abstract : A bioctahedral Ag10 kernel is locked by a pair of Mo7 O26 10− anions to form an inner Ag10 @(Mo7 O26 )2 core which is further encapsulated by an outer Ag70 shell to form three-shell Ag10 @(Mo7 O26 )2 @Ag70 nanoclusters. Abstract : Controlled trapping atom-precise ultrasmall silver nanoparticles into silver nanoclusters is challenging; thus only limited progress has been made in this area. We are therefore inspired to isolate two novel silver nanoclusters, Ag10 @Ag70 (SD/Ag80a andSD/Ag80b ; SD = SunDi), where a novel fcc-structured Ag10 kernel built from two single-edge opened Ag6 octahedra by sharing one edge is trapped. The bioctahedral Ag10 kernel is locked by a pair of Mo7 O26 10− anions to form an inner Ag10 @(Mo7 O26 )2 core which is further encapsulated by an outer Ag70 shell to form three-shell Ag10 @(Mo7 O26 )2 @Ag70 nanoclusters. Notably, the bioctahedral Ag10 kernel has not been observed in silver nanoclusters ever before, thus representing a new embryo state of silver nanoparticles.SD/Ag80a emits in the near infrared (NIR) region ( λ em = 730 nm) at low temperature. This work will deepen our understanding on the atomic-level growth of silver nanoparticles and complicated three-shell self-assembly involving polyoxometalate (POM) and two different silver nanoclusters.